2015
DOI: 10.1093/ijnp/pyu070
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Prevents Brain Toll-Like Receptor 4 Pathway Activation and Neuroinflammation in Rat Models of Acute and Chronic Restraint Stress

Abstract: Background:Alterations in the innate immune/inflammatory system have been proposed to underlie the pathophysiology of psychotic disease, but the mechanisms implicated remain elusive. The main agents of the innate immunity are the family of toll-like receptors (TLRs), which detect circulating pathogen-associated molecular patterns and endogenous damage-associated molecular patterns (DAMPS). Current antipsychotics are able to modulate pro- and anti-inflammatory pathways, but their actions on TLRs remain unexplor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, NRF2 knockdown in astrocytes abrogated the neuroprotective effect of 15d-PGJ 2 , as well as 15d-PGJ 2 -facilitated ARE-dependent antioxidant enzyme gene induction [9]. Both pathways are regulated by paliperidone in animal models of acute/chronic stress and could be implicated, at least in part, in the effects reported here [25,29].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, NRF2 knockdown in astrocytes abrogated the neuroprotective effect of 15d-PGJ 2 , as well as 15d-PGJ 2 -facilitated ARE-dependent antioxidant enzyme gene induction [9]. Both pathways are regulated by paliperidone in animal models of acute/chronic stress and could be implicated, at least in part, in the effects reported here [25,29].…”
Section: Discussionmentioning
confidence: 80%
“…Vetoquinol®, Madrid, Spain). Paliperidone was chosen in the present study considering previous reports have showed an immunomodulatory role of paliperidone in animal models based on acute/chronic stress exposure [25]. The dose of paliperidone (1 mg/kg) was chosen on the basis of previous in vivo determinations of signaling pathways related to oxidative stress, cytokines, and synaptic plasticity in the PFCof Sprague-Dawley rats [26].…”
Section: Drug Administration and Experimental Designmentioning
confidence: 99%
“…Another example illustrating the role of antipsychotic drugs is the study of the effect of paliperidone in neuroinflammation. The authors show that the pre-treatment of rats with paliperidone inhibited the stimulation of toll-like receptor 4 (TLR4) in a model of neuroinflammation induced by stress (Macdowell et al, 2014). In the same direction, another study has shown that haloperidol attenuates the activation of NF-kB, and consequently abrogated the production of pro-inflammatory cytokines in macrophages in response to lipopolysaccharide (LPS) (Yamamoto et al, 2016).…”
mentioning
confidence: 93%
“…26 Finally, paliperidone regulates stress-induced activation of TLR4 in animal models. 27 Taking into consideration all this background, in the present study we aimed to determine and report putative modifications of the TLR4 signalling pathway by using 2 different approaches: 1) quantification of protein and mRNA expression in postmortem prefrontal cortex (PFC) samples and 2) genetic association analysis to identify single nucleotide polymorphisms (SNPs) associated with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%